HAK KEWARISAN WARGA NEGARA INDONESIA YANG DIADOPSI OLEH WARGA NEGARA ASING BERDASARKAN HUKUM ISLAM - Melati Puspasari Erlandita (Fakultas Hukum, Universitas Gorontalo, 2021)
To fulfill spiritual and physical needs, humans need and want to have offspring for continuation of their offspring so that they do a marriage with another human being, in order to get offspring. In a marriage, a child is needed to continue the offspring. Adoption is a method that's easiest to find in their environment because there are married couples who don't have children or wanting to help other families who also don't have children or because of other factors. In Islam, permitted adoption of a child is an adoption that does not attach the lineage to the adopted children, so that their position does not affect the inheritance. The adoption process that foreigners are prohibited from being carried out directly by the biological parents because the adoption must be at a childcare institution. The purpose of this article is to find out the process of adoption by foreigners based on the Compilation of Islamic Law and to find out the inheritance rights for adopted children of Indonesian citizens who are adopted by foreign citizens based on the Compilation of Islamic Law. The type of research used is normative juridical with a statute approach. The result of this research is that the status of an adopted child cannot be used as a biological child, but the relationship is limited to the maintenance of the child and the inheritance rights still come from the biological parents. Meanwhile, the adoptive parents only provide a will and one third of the inheritance